PENGARUH LAMA WAKTU PENYANGRAIAN TERHADAP STANDAR MUTU BIO-OIL KACANG TANAH (Arachis hypogea L) DENGAN METODE MANUAL PRESSING: The Effect of Roasting Time on The Quality of Peanut (Arachis Hypogea L) Bio-Oil Using The Manual Pressing Method - Ellis Marisa; Bagus Setyawan; Arfiati Ulfa Utami (Program Studi Teknologi Hasil Pertanian Universitas PGRI Banyuwangi, 2023)
Cooking oil is an important food ingredient for Indonesians, but in recent years, oil shortages have caused significant price increases. Therefore, this research tries to utilize peanuts to produce oil that can be used in daily activities, especially in the kitchen, as well as testing its characteristics in accordance with bio-oil quality standards. The research method used was experimental by testing the effect of roasting time on various characteristics of peanut oil, including water content, viscosity and free fatty acid content. The results showed that roasting time had a significant effect on all parameters tested. A roasting time of 25 minutes produces peanut oil with a low moisture content (3.3%) and a lower viscosity (44.5 cP). Although the quality of peanut oil in terms of moisture content and viscosity is classified as good, the free fatty acid content test shows that P3 with a duration of 45 minutes has a free fatty acid content of 11.7% which exceeds the threshold according to the SNI standard for cooking oil, namely 2 %.